Effect of highway ramp separation on traffic flow: An investigation using Monte Carlo simulation - Wong X.C.; Jamesy J.A.; Ramasamyz A.K.; Ahmedx S.K. (2023)
Due to urbanization, the number of vehicles on roads has increased to an alarming level causing congestions to happen frequently. Highways are built to ease these congestions that happen due to heavy traffic. However, it is necessary to evaluate the effectiveness of these highways. In this paper, a simulation model of a highway system with two ramps is developed using Markov Chain Monte Carlo technique. The model is then used to study the effect of ramp locations on the highways. The effect due to two important parameters, namely the separation between the ramps and the number of vehicles entering the system, is investigated here. The performance of this system is measured in terms of average delay experienced by the vehicles. Results obtained indicate that traffic behavior on the highway can be modeled accurately using this method. 2010 IEEE.